Quality Analysis of Fresh Vegetable Product with Prima Certificate (Case Study Of Nagari Padang Lua Kecamatan Banuhampu Kabupaten Agam) - Rina, Pebrina Rohayati; Tuty Anggraini; Deivy Andhika Permata (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Referring to the Indonesian National Standard (SNI), fresh food quality parameters must have certain physical quality criteria, free from pesticide residues, microbial contamination and free of heavy metal contamination. The purpose of the study was to analyze the quality of red chili peppers, spring onions, cabbage, eggplant and chickpeas that have been certified prima with 3 (three) testing parameters, namely testing the physical quality of vegetables referring to SNI 01-4480-1998 for red chili products, SNI 01-6996-2004 for spring onion products, SNI 01-3174: 1992 for cabbage products, SNI 3163: 2014 for purple eggplant and chickpea products. Lead heavy metal contamination testing refers to SNI 7387:2009 and microbiological contamination testing refers to SNI 7388:2009. The research was conducted in the Nagari Padang Lua area, Kecamatan Banuhampu, Kabupaten Agam on 5 vegetable cultivation businesses that have been certified as prima. The research method used was descriptive testing. The results showed that there were deviations in the physical quality of fresh red chilies, namely the level of uniformity of the size of red chilies that were below the SNI quality standard (92.33%), very high levels of impurities in leaf onions, total microbial contamination (ALT) in leaf onions and cabbage/cabbage exceeded the maximum limit of total contamination allowed in food, namely 1.39x104 and 1.708x104 E.Coli contamination was detected exceeding the maximum limit of contamination in chickpeas which was 3/gr, while for lead contamination (P4), the total microbial contamination (ALT) in leaf onions and cabbage exceeded the maximum limit of total contamination allowed in food, respectively.